Ethno‐National Narratives of Human Rights: The Northern Ireland Policing Board. Issue 1 (11th September 2019) - Martin, Richard
Abstract: Policing in Northern Ireland has undergone one of the world's most extensive human rights reform programmes. The challenge has been whether the human rights paradigm can serve as a mutual basis for the region's sparring ethno‐national communities to deliberate over long‐contested issues of policing, accountability and justice. This article focuses on the Northern Ireland Policing Board as an arena to examine the contemporary political attitudes and agendas that animate the Board's statutory duty to monitor policing on the basis of human rights. Marshalling qualitative data and drawing on legal anthropology, this article offers an account of the 'social life' of human rights and policing in the context of Northern Ireland's imperfect peace. It argues that, irrespective of legal standards, human rights oversight harbours deep sentiments and concerns, at the heart of which are communities' own historical engagements with rights, competing legacies of the conflict and divergent understandings of contemporary policing.